Analisis Yuridis Putusan Pailit PT Sritex dan Implikasi Hukumnya terhadap Perlindungan Karyawan Serta Keberlangsungan Usaha - Manohara, Safa; Hania, Sally; Zevanya, Keisha; Tarina, Dwi Desi Yayi (Media Hukum Indonesia (MHI), 2026)
Bankruptcy is a very undesirable situation for a company, considering that the losses it causes are not only felt by the company itself but also by various stakeholders, especially workers and creditors. This research focuses on the bankruptcy decision handed down to PT Sritex in October 2024, which has a significant impact on employee rights and the company's business continuity. The method used is normative juridical with a case study, which examines the provisions of national law related to bankruptcy and Suspension of Debt Payment Obligations, as well as analyzes court decisions and related legal documents. The findings of the study show that although Sritex has made various efforts to resolve its obligations to employees, including the payment of BPJS salaries and contributions, challenges related to the payment of workers' rights such as severance pay and other compensation remain. This study also highlights that although Law Number 37 of 2004 regulates the protection of business continuity through the principle of business continuity and the PKPU mechanism, implementation in the field often faces structural, technical, and institutional constraints, including suboptimal curatorial supervision and limited transparency from debtors. Therefore, this study recommends strengthening the role of curators and increasing debtors' financial transparency as key factors in the optimal application of the principle of business continuity as an instrument of legal protection while supporting business sustainability. The contribution of this study lies in a deeper understanding of the dynamics of bankruptcy in Indonesia and its legal implications for worker protection and business continuity..